2021
DOI: 10.3390/ijerph18052296
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Air Quality and Covid-19 Lockdown Measures in Valencia, Spain

Abstract: The set of measures to contain the diffusion of COVID-19 instituted by the European governments gave an unparalleled opportunity to improve our understanding of the transport and industrial sectors’ contribution to urban air pollution. The purpose of this study was to assess the impacts of the lockdown measures on air quality and pollutant emissions in Valencia, Spain. For this reason, we determined if there was a significant difference in the concentration levels of different particulate matter (PM) sizes, PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 37 publications
(48 reference statements)
6
20
1
1
Order By: Relevance
“…The COVID-19 pandemic led to an improvement in air quality and therefore benefited people’s health, consistent with the conclusions of Berman and Ebisu [ 42 ], Singh and Chauhan [ 43 ], Stratoulias and Nuthammachot [ 44 ], Nadzir et al [ 45 ], Nakada and Urban [ 46 ], Ma and Kang [ 47 ], and Donzelli et al [ 48 ]. They all presented evidence of the bettering of the air quality over large metropolitan areas during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 79%
“…The COVID-19 pandemic led to an improvement in air quality and therefore benefited people’s health, consistent with the conclusions of Berman and Ebisu [ 42 ], Singh and Chauhan [ 43 ], Stratoulias and Nuthammachot [ 44 ], Nadzir et al [ 45 ], Nakada and Urban [ 46 ], Ma and Kang [ 47 ], and Donzelli et al [ 48 ]. They all presented evidence of the bettering of the air quality over large metropolitan areas during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 79%
“…The LD measure effects on the PM10 and PM2.5 concentrations were highly site-dependent, according to previous studies, either because each site has its own specific characteristics (e.g., type, meteorology, anthropogenic activities) or because of the different LD measures adopted by the different countries. Monitoring stations in urban sites such as Milan [54], Florence [13], Athens [55], Barcelona [56], and Baghdad [57] experienced a significant PM decrease due to the LD measures, since the PM pollution was strictly related to the anthropogenic activities at these sites, as we found at Sites 4 and 7. Conversely, other studies reported PM concentration increases during the LD periods, as summarized by [58].…”
Section: Pm Mass Concentrations Before During and After The Lockdownsupporting
confidence: 57%
“…The authors have observed reductions of 50%, 34%, and 20% at urban traffic, urban background, and rural background stations, respectively. Similarly, Donzelli et al (2021) [23], nitric oxide levels were significantly reduced in seven air monitoring stations placed in the city of Valencia, Spain. Considerable NO 2 concentration variations between before and during the lockdown have been shown by several studies, like Mahato et al (2020) [24], in which a reduction of 52.68% is documented.…”
Section: Nitrogen Dioxidementioning
confidence: 61%